2009
DOI: 10.1128/aac.01653-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Profiling of Ceftobiprole for Treatment of Complicated Skin and Skin Structure Infections

Abstract: Ceftobiprole, a broad-spectrum cephalosporin with activity against methicillin (meticillin)-resistant staphylococci, was statistically noninferior to a combination of vancomycin plus ceftazidime in patients with complicated skin and skin structure infections (cSSSI). This analysis used data from this clinical trial to determine the relationship between therapeutic outcome and the percentage of time that the unbound ceftobiprole concentration exceeds the MIC (percent T>MIC). From the trial of ceftobiprole (500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…In contrast, ceftobiprole and dalbavancin were superior to all investigated agents and had 100% likelihood of target attainment. This corroborates the results of other clinical and pharmacodynamic studies that showed the therapeutic value of these two agents …”
Section: Discussionsupporting
confidence: 91%
“…In contrast, ceftobiprole and dalbavancin were superior to all investigated agents and had 100% likelihood of target attainment. This corroborates the results of other clinical and pharmacodynamic studies that showed the therapeutic value of these two agents …”
Section: Discussionsupporting
confidence: 91%
“…Similar to the exposure-response relationship found for other antimicrobials (6,7,16,17), the relationship found here indicates that optimal exposure increases the likelihood of microbiological eradication. In patients with insufficient exposure to ceftobiprole, the probability of microbiological eradication is approximately 44%, whereas the probability of microbiological eradication in patients with an exposure of 100% is 91%.…”
Section: Discussionsupporting
confidence: 68%
“…Observed target attainment rates for Asian (n = 47) and non-Asian (n = 152) subjects for targets of concentrations above the MIC, ranging from 40%-100% of the dosing interval. 16 We therefore calculated the exposure for fT >MIC to be 30%-100% and concluded that for all these different targets, the exposure in the 2 subgroups was comparable. and in human data.…”
Section: Discussionmentioning
confidence: 99%